DAMPAK NEGATIF PEMANFAATAN APLIKASI TIK-TOK DI KALANGAN REMAJA DESA MATA IE KABUPATEN ACEH BARAT DAYA - Hijrah; Nurul Intan (Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2021)
The Tik-Tok application has positive and negative effects on teenagers in Aceh, many teenagers are able to express themselves and share positive activities using the Tik-Tok application, and vice versa, many teenagers make the wrong use of this social media platform so that it has a negative impact. for yourself and those around you. This research was conducted because there was a change in the behavior of the youth of Mata Ie Village, Southwest Aceh Regency who used the Tiktok application, the study was conducted with a qualitative approach with data collection techniques through interviews with village heads, youth leaders, and parents of teenagers using the Tik-Tok application. From the results of research conducted, the negative impact of using the Tik-Tok application by Youth in Mata Ie Village, Southwest Aceh Regency is due to the lack of supervision and the role of various community leaders in making appeals and guidance in the use of social media, especially the Tik-Tok application.